Fetal soft tissue edema and nuchal region with septations: Case report (Research, Society and Development, 2023)
During the prenatal period, a series of crucial exams are conducted with the aim of preventing and early detecting possible pathologies that could affect the health of the mother and fetus. Among these exams, the 1st trimester morphological ultrasound stands out, which is essential for evaluating the measurement of nuchal translucency (NT). When NT is less than 2.5 mm, it is considered within normal limits. However, as this measurement increases, the risk of aneuploidy increases, varying from 0.3% in cases below 3.5 mm to a notable increase, reaching 64% when the measurement exceeds 6.5 mm. This study's main objective is to report a case that involved changes in the nuchal translucency of a fetus at 11 weeks of gestation. These changes were initially described as fetal soft tissue edema and the presence of septations in the nuchal region, however, they were no longer identified during the second examination. The present work is a case report, with the protagonist being a female patient, 33 years old and in her first pregnancy. Furthermore, this study will detail the patient's prenatal follow-up, documenting it from the first weeks of pregnancy until the moment of birth, providing a comprehensive and in-depth view of the clinical implications involved in this specific case, showing that even in the face of changes in image, we can have a healthy baby without repercussions on his body even with an altered NT.